2005
DOI: 10.1002/mc.20115
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin inhibits oxidative stress‐induced macromolecular damage in N‐nitrosodiethylamine (NDEA)‐induced hepatocellular carcinogenesis in Wistar albino rats

Abstract: Apigenin (4',5,7-trihydroxyflavone), a flavone subclass of flavonoid widely distributed in many herbs, fruits, and vegetables is a substantial component of the human diet and has been shown to possess a variety of biological activities including tumor growth inhibition and chemoprevention. Recent studies in several biological systems have shown that apigenin induces tumor growth inhibition, cell cycle arrest, and apoptosis. Free radical-induced degradation of polyunsaturated fatty acid results in electrophilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 50 publications
5
34
0
3
Order By: Relevance
“…Several recent studies have shown that apigenin has antiapoptotic and antioxidative properties in a variety of in vitro and in vivo systems. [26][27][28] To the best of our knowledge, this is the first report that apigenin attenuates dRib-induced oxidative cell damage in pancreatic β-cells, which may promote cell recovery under oxidative stress conditions.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Several recent studies have shown that apigenin has antiapoptotic and antioxidative properties in a variety of in vitro and in vivo systems. [26][27][28] To the best of our knowledge, this is the first report that apigenin attenuates dRib-induced oxidative cell damage in pancreatic β-cells, which may promote cell recovery under oxidative stress conditions.…”
Section: Resultsmentioning
confidence: 79%
“…Apigenin has been shown to have antiapoptotic and antioxidative properties in a variety of in vitro and in vivo systems. [26][27][28] With respect to the regulation of diabetes, apigenin is known to inhibit high glucose levels and tumor necrosis factor-α (TNF-α)-induced adhesion molecule levels in human endothelial cells. 29) It has also been noted that apigenin has the potential to regulate diabetes as well as disease-induced thyroid dysfunction and lipid peroxidation.…”
mentioning
confidence: 99%
“…The results indicate that both flavonoids exhibited cell growth inhibitory effects which were due to cell cycle arrest and down-regulation of the expression of CDK4 with induction of p53 and p21, respectively. In addition, Jeyabal et al (115) have shown the in vivo protective effects of apigenin on N-nitrosodiethylamine-induced and phenobarbitol promoted hepatocarcinogenesis in Wistar albino rats. Apigenin treatment at 25 mg/kg body weight for two weeks to these rats provided protection against the oxidative stress and DNA damage caused by the carcinogen.…”
Section: Apigenin and Leukemiamentioning
confidence: 99%
“…Free radical scavenging property of apigenin depends on the number of OH groups present at 4, 5 and 7th positions of its C-ring structure (Sharma et al, 2012). The antioxidant property of apigenin has been reported due to double bond between the C 2 and C 3 carbon atoms of the C-ring and presence of oxo group in 4th position of C-ring (Jeyabal et al, 2005) (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%